Digitalisasi Sebagai Strategi Revitalisasi Usaha Mikro Kecil dan Menengah (UMKM) di Masa Pandemi Covid-19 - Ismail Ismail; Saiful Bahgia (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2021)
The Covid-19 pandemic has had a huge impact on various sectors, especially the economic sector, including the existence of MSMEs that have played an important role in Indonesia's economic development. This study aims to analyze how digitalization has become a strategy for developing MSMEs in the era of the Covid-19 pandemic and to understand the urgency of using e-marketing to encourage the sustainability of MSMEs by taking the example of digital platform-based MSMEs. This research uses qualitative methods, descriptive analysis methods, and contextual techniques. The data collected is supporting data from literature research and relevant online reporting documents. This research concludes that the implementation of digitalization and e-marketing through the marketplace carried out by MSME entrepreneurs is considered very necessary so that business activities can continue and generate economic value in the midst of a pandemic as it is today.